Agreement on urgency assessment between secretaries and general practitioners: an observational study in out-of-hours general practice service in Belgium. Issue 5 (3rd September 2015) - Philips, H.; Van Bergen, J.; Huibers, L.; Colliers, A.; Bartholomeeusen, S.; Coenen, S.; Remmen, R.
Abstract : Background: In some European countries telephone triage (TT) during out-of-hours primary care showed to be safe and effective. Other countries, such as Belgium, may not have trained auxiliary personnel while their national health services want to establish TT. Objectives: To compare urgency levels assessed by secretaries and general practitioners in one general practice cooperative in Belgium. Methods: Percentage of correct-, under-, and over-triage were calculated in total and per reason for encounter. Inter-rater agreement was investigated. Results: The secretaries correctly triaged (same urgency level) 77% of the telephone calls, under-triaged 10% and over-triaged 13%.'Shortness of breath', 'skin cuts', 'chest pain', 'feeling unwell' and 'syncope' were often under-triaged. Conclusion: Before introducing TT, auxiliary staff should be trained and protocols should be used.